Impact of reservoir wettability and heterogeneity on CO2-plume migration and trapping capacity - Al-Khdheeawi, Emad A.; Vialle, Stephanie; Barifcani, Ahmed; Sarmadivaleh, Mohammad; Iglauer, Stefan (Elsevier, 2017)
Reservoir wettability – the tendency of a rock surface to be in contact with one fluid more than other fluids – can vary substantially from strongly water-wet to strongly CO2-wet. However, the influence of such differences in wettability on the CO2 storage capacity has received little attention. Here, we studied the impact of reservoir wettability on CO2 plume behaviour and residual and solubility trapping capacities. We also compare the case of a homogeneous distribution of permeability and porosity values within the reservoir with that of a heterogeneous distribution. We found that CO2-wet reservoirs have the highest CO2 vertical migration, while water-wet reservoirs best retain CO2. In addition, less residual CO2 but more dissolved CO2 is obtained in a CO2-wet reservoir. Furthermore, we demonstrate that reservoir heterogeneity reduces the vertical CO2 migration and induces significant horizontal migration, while lower residual and solubility storage capacities are achieved. We thus conclude that both reservoir wettability and heterogeneity significantly impact CO2 migration and trapping capacities and need to be incorporated into reservoir simulations for accurate predictions of both CO2 plume behaviour and CO2 storage capacities. Overall, we conclude that strongly water-wet reservoirs are preferable CO2 sinks.